(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study has been conducted to find out the mechanism and effect of basalt fiber on compacted soil. For this study a series of Unconfined Compressive Strength, California Bearing Ratio tests, Atterberg limits and Proctor compaction tests have been conducted on soil reinforced with basalt fiber. The various contents of basalt fibers are considered in this paper. Fibers are dispersed into respective soil at contents of 0.15%, 0.20%, 0.25 and 0.30%, under constant length of 12 mm, experimental results shows that basalt fiber can effectively improve the Atterberg’s limits, UCS and CBR of reinforced soil. The results have shown that the Maximum Dry density of soil increases by 18.01% when 0.30% of basalt fibers mixed with the given soil. The Unconfined compressive strength of soil also increases by 380% when 0.30% of basalt fibers were mixed in the soil sample. The best content was found at 0.15% of basalt fiber were MDD, UCS and CBR values of soil increases rapidly. The study has shown that the strength of soil increases with the inclusion of basalt fibers by reducing the liquid limit and plastic limit, The plasticity index decreases by 62.64% which indicates that the properties of soil being improved.